Effectiveness of an educational program on nurses' knowledge regarding management of extravasation vesicant intravenous chemotherapy at oncology centers in Baghdad city - hussein, batool; Mansour, khalida (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: to determine the effectiveness of an Education Program on Nurses' Knowledge regarding management of extravasation vesicant intravenous chemotherapyMethodology: quiz-experimental study (single-group pretest-posttest1 and posttest2) was directed in Amal oncology center and national oncology center in Baghdad city from 13th, December 2018 to the 7 of February 2019. The program and tool have been created by the researcher for the purpose of the study. A non- probability purposive sample of (40) nurses who employed in Baghdad oncology centers. Validity and reliability of the instrument were determined through a pilot study. Data were analyzed through the use of Statistical Package for Social Sciences (SPSS) version. Descriptive and inferential statistical measures were employed.Results: The study results of pre-test for the participants of nurses revealed poor knowledge regarding overall management extravasation. While the results of post- 1 test exposed that the improved knowledge and stability by post 2 test indicated the positive effect of the education program about management extravasation..Recommendations: The researcher recommends a vital need of generalization of all the centers and hospitals that are given chemotherapy for educational and awareness program about management extravasation for nursing staff Regardless of gender and age difference.